Impact of Reduced Chemical Fertilizer and Organic Amendments on Yield, Nitrogen Use Efficiency, and Soil Microbial Dynamics in Chinese Flowering Cabbage - Jiaxin Xu; Jianshe Li; Xia Zhao; Zhen Liu; Hao Xu; Kai Cao; Lin Ye (Horticulturae)
(1) Background: The escalating issue of soil degradation caused by excessive chemical fertilizer application poses significant threats to the sustainable development of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis (L.) var. utilis Tsen et Lee) production. This research aimed to identify the impacts of reduced chemical fertilizer application integrated with organic amendments on cabbage yield and rhizosphere soil microenvironment characteristics. (2) Methods: A biennial field experiment was conducted during the 2022–2023 growing seasons at Lijun Town, Yinchuan City, Ningxia Hui Autonomous Region. Five treatments were tested: (i) Control (CK, no fertilizer); (ii) Conventional chemical fertilization (CF1, chemical fertilizer only); (iii) Reduced chemical fertilization (CF2, 30% less chemical fertilizer); (iv) CF2 + Well-decomposed chicken manure (FCM, 30% less chemical fertilizer + rotted chicken manure); and (v) CF2 + Vermicompost (FEM, 30% less chemical fertilizer + vermicompost). (3) Results: In 2023, the FCM treatment reduced electrical conductivity (EC) by 24.80% and pH by 2.16%, while the FEM treatment decreased EC by 31.13% and pH by 3.84% compared to controls. The FEM treatment significantly enhanced total nitrogen content by 12.71% and 8.85% relative to CF1 and FCM treatments, respectively. Compared to CF1, FEM increased soil organic matter content by 10.49% in 2022 and 11.24% in 2023. Organic fertilizer amendments elevated available nitrogen, phosphorus, and potassium levels while enhancing sucrase activity: FCM and FEM treatments increased sucrase activity by 23.62% and 32.00%, respectively, in 2022. Organic fertilization improved bacterial diversity and richness, optimized microbial community structure, and increased the relative abundance of Bacillus. It also upregulated microbial metabolic pathways related to carbohydrate and amino acid metabolism. Soil nutrients and bacterial community structure showed positive correlations with yield, whereas soil enzyme activities exhibited negative correlations. Key factors influencing yield were identified as Proteobacteria, Chloroflexi, available potassium, organic matter, available nitrogen, Actinobacteria, Firmicutes, total nitrogen, pH, and sucrase activity. (4) Conclusions: Integrated analysis of yield and soil microenvironmental parameters demonstrates that the fertilization regimen combining 30% chemical fertilizer reduction with vermicompost amendment (FEM) constitutes a more efficient fertilization strategy for Chinese flowering cabbage, making it suitable for regional promotion in the Ningxia area.